1998
DOI: 10.1191/096120398678920253
|View full text |Cite
|
Sign up to set email alerts
|

Anti-β2-glycoprotein I and anti-prothrombin antibodies in patients with the ‘antiphospholipid’ syndrome: Immunological specificity and clotting profiles

Abstract: Lupus anticoagulant (LA) antibodies have been shown to be directed to protein-phospholipid complexes. In this study, we report on LA antibodies from patients with the 'antiphospholipid' syndrome (APS), that are directed to prothrombin and beta2-glycoprotein I, but not to the complexes of these plasma proteins to anionic phospholipids. The anti-prothrombin antibodies studied had different reactivities in two clotting assays: the dilute Russell's viper venom time (dRVVT) and the dilute kaolin clotting time (dKCT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 30 publications
2
6
0
Order By: Relevance
“…This is consistent with inhibition of PL binding to aPL described previously during protozoal infections and presumably due to the interference of peptidic co‐factors such as β2 GPI with antigenic interactions of aCL [11,12]. Anti‐β2 GPI antibodies were found in a small number of malaria‐exposed donors, which confirms that they are usually not detected during infectious diseases, while in APLS they are considered as more specifically associated with clinical manifestations [10,30–33].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This is consistent with inhibition of PL binding to aPL described previously during protozoal infections and presumably due to the interference of peptidic co‐factors such as β2 GPI with antigenic interactions of aCL [11,12]. Anti‐β2 GPI antibodies were found in a small number of malaria‐exposed donors, which confirms that they are usually not detected during infectious diseases, while in APLS they are considered as more specifically associated with clinical manifestations [10,30–33].…”
Section: Discussionsupporting
confidence: 89%
“…A comparatively limited number of studies are currently available on malaria‐associated aPL [16]. High prevalence was reported in naive donors and inhabitants of P. falciparum or vivax endemic areas (35% and 34% in patients from Nigeria and South Africa, respectively) [5,32]. Travellers returning to London from Africa presented a 79% prevalence, close from present results [6].…”
Section: Discussionsupporting
confidence: 81%
“…In addition, Pengo et al [102] have demonstrated that purified anti-2-GPI display LA activity prolonging dRVVT only in the presence of PLs, and they proposed to perform dRVVT with and without PLs to identify specific antibodies populations with LA activity. On the other hand, it has been shown that purified anti-II from different patients show different reactivity on dRVVT or KCT: some anti-II prolong mainly dRVVT and some anti-2-GPI KCT [103]. The dRVVT profile was associated with thrombosis in a prospective evaluation of 100 patients with LA during a median follow-up of 37 months [104].…”
Section: Coagulation Profiles Of La In the Recognition Of Thrombosis mentioning
confidence: 98%
“…In addition, Pengo et al [56] demonstrated that purified anti-β 2 GPI display LA activity prolonging dRVVT only in the presence of phospholipids, and they proposed to perform dRVVT with and without phospholipids to identify specific antibody populations with LA activity. On the other hand, it has been shown that purified anti-PT from different patients show different reactivity on dRVVT or KCT: some anti-PT prolong mainly dRVVT and some anti-β 2 GPI the KCT [57]. Recently two methods to discriminate β 2 GPI-dependent LA from β 2 GPI-independent LA activity were proposed [58,59].…”
Section: Immunological Specificities and Properties Of Anti-β 2 Gpi Amentioning
confidence: 98%
“…Anti-β 2 GPI is a polyclonal heterogeneous population of immunoglobulins composed of subpopulations which differ in their biological activities, avidity, and target different epitopes on the β 2 GPI molecule [33][34][35]. During the last years, various potential epitopes on β 2 GPI have been identified and they seem to spread all over the five domains of the molecule [36].…”
Section: Immunological Specificities and Properties Of Anti-β 2 Gpi Amentioning
confidence: 99%